A kind of anti-coking and anti-ash coating for the receiving surface of waste heat boiler and its preparation method

By using paints of inorganic and organic hybrid aqueous epoxy resin and silicon sol on the heated surface of the waste heat boiler, and performing a combination reaction in high-temperature flue gas, the problem of easy coking and ash on the heated surface of the waste heat boiler is solved, and the effect of improving heat transfer performance and heat exchange ability is achieved.

CN117004291BActive Publication Date: 2025-03-07四川陆亨能源科技有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311023487.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-15
Publication Date
2025-03-07
Estimated Expiration
2043-08-15

AI Technical Summary

Technical Problem

The heated surface of the existing waste heat boiler is prone to coke and ash, resulting in poor heat transfer effect. It is necessary to first treat the rust-coking and anti-gray coating before spraying anti-coking and anti-gray coating.

Method used

A mixture of inorganic organic hybrid aqueous epoxy resin and a silica sol is used as the substrate, and tanninic acid, phosphoric acid, sodium molybdate, sodium chloride, hydrophobic nanosilica, fluorocarbon emulsion and graphene are added, and the coating is sprayed and combined in a flue gas of 500 to 600°C to form a coating that is anti-coking and ash.

Benefits of technology

This coating can effectively prevent the heat-receiving surface from coking and ashing without using rust coating converters, improve heat transfer performance, enhance the strength and heat resistance of the coating, reduce the emission of harmful gases, and improve heat exchange ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117004291B_ABST
    Figure CN117004291B_ABST
Patent Text Reader

Abstract

The present invention discloses an anti-coking and anti-ashing coating for the heating surface of a waste heat boiler and a preparation method thereof, and relates to the technical field of boiler heating surface coatings. The anti-coking and anti-ashing coating for the heating surface of a waste heat boiler and the preparation method thereof utilize tannic acid, phosphoric acid, and sodium molybdate in the formula to react with the rust on the heating surface at 500 to 600°C to form a solid foundation, thereby eliminating the need to use a rust coating converter to treat the rust on the heating surface; in addition, chlorinated wax, hydrophobic nano-silicon dioxide, and fluorocarbon emulsion in the formula can maintain the coating's ability to improve the coating's hydrophobic angle; and finally, graphene is evenly distributed in the coating to form a multi-layer ring pore structure to improve heat transfer performance, and there is a significant improvement in heat transfer during long-term use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of boiler heating surface coatings, and in particular to a waste heat boiler heating surface anti-coking and anti-ash coating and a preparation method thereof. Background Art

[0002] Due to the particularity of the production system and the waste heat power generation thermal system, the waste heat boiler mainly plays the following roles in the entire system:

[0003] (1) It plays a role in lowering the temperature of the entire flue gas, ensuring the normal operation of the dust removal equipment in the system and achieving low-temperature and environmentally friendly flue gas discharge;

[0004] (2) The waste heat boiler generates high-temperature and high-pressure steam by utilizing waste heat, and then drives the gas turbine and generator to generate electricity through integration with the supplementary combustion boiler, for example, to provide power for the entire cement and silicon production power production system equipment;

[0005] (3) Waste heat boiler coating has various waste heat boiler heating anti-coking and anti-ashing functions and their applications;

[0006] (4) It has a certain self-dust removal effect, and the separated dust can be recycled.

[0007] However, the amount of flue gas from the waste heat boiler is large, and the heat required for steam and saturated water mainly comes from the flue gas. The auxiliary burner requires less air, but the amount of flue gas that needs to be cooled is very large. A small amount of air is difficult to effectively dissipate the heat in the flue gas. If an air preheater is installed, not only is the amount of heat recovered small, but the required heat transfer area is also very large, and its economic benefits are bound to be very poor.

[0008] Therefore, how to improve the thermal conductivity, anti-ashing and anti-coking performance of the heating surface of the waste heat boiler is conducive to greatly improving the efficiency of the waste heat boiler.

[0009] In the prior art, for example, the invention with publication number CN102351553A discloses an anti-coking coating for a water-cooled wall guard belt. Although the invention patent solves the technical problem of anti-coking for a water-cooled wall guard belt, it cannot be applied to the anti-coking and anti-ashing of the receiving surface of a waste heat boiler.

[0010] In addition, in the prior art, for the rusty heating surface, it is necessary to first spray the rusty heating surface with a rust coating conversion agent and then spray the anti-coking and anti-ashing coating. Summary of the invention

[0011] 1. Technical issues to be solved

[0012] In view of the shortcomings of the prior art, the present invention provides a waste heat boiler surface anti-coking and anti-ash coating and a preparation method thereof, which solves the following technical problems:

[0013] 1. The existing waste heat boiler flue heating surface is prone to coking and ash formation, resulting in poor heat transfer effect;

[0014] 2. The existing waste heat boiler coating needs to be sprayed with a rust coating converter on the rusty heating surface before the anti-coking and anti-ash coating is sprayed.

[0015] (II) Technical solution

[0016] Weighing - batching - mixing - neutralization - unloading - standby

[0017] Weigh the materials with an electronic scale, add measured water, inorganic-organic hybrid waterborne epoxy resin and silica sol mixture into a four-mouth flask equipped with a stirrer, a constant pressure funnel and a condenser, stir quickly, adjust the appropriate stirring speed when the temperature rises to 75 degrees, stir for 20-60 minutes, add defoamer if there are bubbles in the resin, the speed is 1500r-1800r / min, stir for 5 minutes, add deionized water according to the state of the coating, and stir for 10 minutes. The amount of deionized water added should be adjusted appropriately according to the weather, coating viscosity and temperature change.

[0018] Cool down to below 40 degrees, add ingredients, dispersant and various fillers at the same time, increase the speed to 3000r / min, stir for 30 minutes, so that the powder particles are dispersed into atomic particles under the action of high shear rate, and reach a dispersed stable state, neutralize well, and unload for standby. The process of temperature dropping from 75 degrees to below 40 degrees is also the process of chemical reaction between materials; increasing the speed is conducive to mixing the ingredients evenly.

[0019] Before spraying, use air to clean the heating surface of the waste heat boiler. No ash or oil, no rust, and no rust. Spraying above 20 degrees, the surface is dry for 4 hours, and the actual dryness is 24 hours. Spraying above 5 degrees, the surface is dry for 8 hours and the actual dryness is 48 hours.

[0020] After the paint is sprayed and dried, 500-600℃ flue gas is introduced to cause the paint to undergo a chemical reaction and form a coating that resists coking and ash formation on the heated surface.

[0021] (III) Beneficial effects

[0022] The present invention provides a waste heat boiler surface anti-coking and anti-ash coating and a preparation method thereof.

[0023] Beneficial effects:

[0024] The waste heat boiler anti-coking and anti-ash coating for the heating surface and the preparation method thereof utilize tannic acid, phosphoric acid and sodium molybdate in the formula to react chemically with the rust on the heating surface at 500-600° C. to form a solid foundation, thereby eliminating the need to use a rust coating converter to treat the rust on the heating surface; in addition, the sodium chloride, hydrophobic nano-silicon dioxide and fluorocarbon emulsion in the formula can maintain the coating's ability to improve the coating's hydrophobic angle; and finally, graphene is evenly distributed in the coating to form a multi-layer ring pore structure to improve the heat transfer performance, and a significant heat transfer improvement is achieved during long-term use. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic diagram of the coating and graphene structure of the present invention.

[0026] In the figure: 1. Heating surface tube; 2. Coating. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Inorganic organic hybrid coatings

[0029] 1. Silica sol: water-based epoxy resin (5:1);

[0030] First, mix water-based epoxy resin and silica sol to make the two composite resins form an inorganic-organic coating base material. The optimal reaction temperature is 35-40 degrees, and the ratio is 5 (silica sol): 1 (water-based epoxy resin). After the reaction, take out 55-70%;

[0031] 2. Tannic acid (50% aqueous solution) 3-10%;

[0032] 3. Phosphoric acid (50% aqueous solution) 0.5-2%;

[0033] 4. Sodium molybdate 0.1-1%;

[0034] 5. Propionic acid 0.5-2%;

[0035] 6. Silicon carbide 0.3um.4-10%;

[0036] 7. Conductive carbon black. 5-10%;

[0037] 8. Graphene 20-40nm. 2-5%;

[0038] 9. Talc 1-18um.3-8%;

[0039] 10. Chlorinated wax 1-3%;

[0040] 11. Hydrophobic nano-silicon dioxide 20-40nm. 0.5-2%;

[0041] 12. Hydrophobic nano titanium dioxide 40nm. 0.5-2%;

[0042] 13 Aluminum oxide 0.3um.3-10%;

[0043] 14. Basalt scale 800 mesh. 1-3%;

[0044] 15. Fluorocarbon emulsion 3-7%;

[0045] 16. Microcrystalline wax emulsion 0.5-2%;

[0046] 17. Dispersant (731a). 0.5-2%;

[0047] 18. Defoaming agent (nxz) 0.2-2%;

[0048] 19. Leveling agent (rm-2020) 0.1-1%;

[0049] 20. Add appropriate amount of ionized water.

[0050] Coating preparation and properties:

[0051] Weighing - batching - mixing - neutralization - unloading - standby

[0052] Weigh the materials with an electronic scale, add measured water, inorganic-organic hybrid waterborne epoxy resin and silica sol mixture into a four-mouth flask equipped with a stirrer, a constant pressure funnel and a condenser, stir quickly, adjust the appropriate stirring speed when the temperature rises to 75 degrees, stir for 20-60 minutes, add defoamer if there are bubbles in the resin, the speed is 1500r-1800r / min, stir for 5 minutes, add deionized water according to the state of the coating, and stir for 10 minutes. The amount of deionized water added should be adjusted appropriately according to the weather, coating viscosity and temperature change.

[0053] Cool down to below 40 degrees, add ingredients, dispersant and various fillers at the same time, increase the speed to 3000r / min, stir for 30 minutes, so that the powder particles are dispersed into atomic particles under the action of high shear rate, and reach a uniformly dispersed suspension and stable state, and then unload for standby. The process of temperature dropping from 75 degrees to below 40 degrees is also the process of chemical reaction between materials; increasing the speed is conducive to mixing the ingredients evenly.

[0054] The coating function is to prevent the heating area of ​​the waste heat boiler from coking and ash formation, and the heating surface mainly has a micro-liquid lotus effect. Before spraying the coating, the heating surface of the waste heat boiler is cleaned with air, and it can be directly sprayed without ash or oil, rust or no rust, with low cost. After spraying, the spraying part is heated with 500-600℃ flue gas.

[0055] After heating, the coating can withstand a long-term temperature of 500 degrees and a short-term temperature of 650 degrees. When sprayed at temperatures above 20 degrees, the surface will dry in 4 hours and the actual drying will take 24 hours. When sprayed at temperatures above 5 degrees, the surface will dry in 8 hours and the actual drying will take 48 hours. The adhesion is level 1, the flexibility is greater than 3 / mm, the impact strength is 65kg·cm, the acid resistance is in 10% sulfuric acid, the weight loss and weight gain in 480 hours is less than 1%, the alkali resistance is in 10% sodium hydroxide solution, the weight loss and weight gain in 480 hours is less than 1%, the wear resistance is 1kg, 1000r, and the wear is 18mg. The heat resistance has no change in thermal shock at 450 degrees. When placed in 20-30 degree water within 5 seconds at 450 degrees, there are no bubbles or cracks. The hardness is h6, the hydrophobic angle is 130, the thermal conductivity is 30w / m·k, the viscosity is 30-50s, the solid content is 20-40 plus or minus 2, the wind impact resistance is

[0056] Among them: tannic acid, phosphoric acid, and sodium molybdate react with the rust on the surface of the heated surface under the reaction of flue gas at 500-600℃ to form a solid foundation, which improves the strength and thermal shock resistance of the coating and does not require the use of rust coating converters. When there is no rust on the heated surface, tannic acid, phosphoric acid, and sodium molybdate react with the oxide layer on the surface of the heated surface under the reaction of flue gas at 500-600℃ to form a solid foundation.

[0057] Graphene is evenly distributed in the coating (e.g. Figure 1 ) forms a multi-layer ring pore structure, which can effectively ensure the thermal conductivity of the coating. The final thermal conductivity of the coating is 30w / m·k.

[0058] Chlorinated wax, hydrophobic nano-silica and fluorocarbon emulsion are used to increase the hydrophobic angle of the coating surface, and the final hydrophobic angle of the coating is 130.

[0059] This patent is aimed at the characteristics of industrial silicon ore-fired furnace waste heat boiler with large flue gas volume, high flue gas temperature, fine smoke dust, and large flue gas dust ratio, which can effectively solve the core technology of heat exchange efficiency and dust accumulation. In December 2020, the core technology of the new product appraisal organized by the Sichuan Provincial Department of Economy and Information Technology reached the domestic advanced level. The patent of this invention has been repeatedly tested and optimized, and the core technology of heat exchange has reached the domestic leading level.

[0060] After resisting ash and coking, the thermal energy conversion is increased by 30% (compared to the short-term measurement results without coating), and the heat exchange capacity is increased by 38% in long-term use (compared to the uncoated).

[0061] During long-term use, due to the distribution of graphene in the coating, heat transfer is accelerated in the coating in a parallel manner. Therefore, recalculating the data after long-term use results in a 38% increase in heat transfer capacity (short-term measurements are mostly performed at measuring points, so the actual increase in heat transfer capacity during long-term use cannot be calculated).

[0062] It should be noted that, in the description of the invention, the directions or positional relationships indicated by the terms "up", "down", "left", "right", "front", "back", etc. are descriptions of the structure of the present invention based on the accompanying drawings, and are only for the convenience of describing the present invention, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as a limitation on the present invention.

[0063] The "first" and "second" in this technical solution are only used to distinguish the names of the same or similar structures, or corresponding structures with similar functions, and are not an arrangement of the importance of these structures, nor do they have a ranking, comparison of size, or other meanings.

[0064] In addition, unless otherwise clearly specified and limited, the terms "installation" and "connection" should be understood in a broad sense. For example, the connection can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, or it can be a connection between the two structures. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood based on the overall idea of ​​the present invention and the specific context of the present solution.

Claims

1. An application of an anti-coking and anti-ashing coating for the heating surface of a waste heat boiler to prevent coking and ashing on the heating surface of the waste heat boiler, characterized in that: The composition comprises the following components in mass proportion: 55-70% inorganic organic coating substrate, ionized water and ingredients, wherein the ingredients include 3-10% 50% aqueous solution of tannic acid, 0.5-0.2% 50% aqueous solution of phosphoric acid, 0.1-1% sodium molybdate, 0.5-2% propionic acid, 4-10% silicon carbide, 5-10% conductive carbon black, 2-5% graphene, 3-8% talc, 1-3% chlorinated wax, 0.5-2% hydrophobic nano silicon dioxide, 0.5-2% hydrophobic nano titanium dioxide, 3-10% aluminum oxide, 1-3% basalt flakes, 3-7% fluorocarbon emulsion, 0.5-2% microcrystalline wax emulsion, 0.5-2% dispersant, 0.2-2% defoamer and 0.1-1% leveling agent; The tannic acid, phosphoric acid and sodium molybdate can react with the rust on the heated surface at 500-600°C to form a solid foundation; The preparation process of the inorganic-organic coating substrate is as follows: First, mix the water-based epoxy resin with silica sol to make the two composite resins form an inorganic-organic coating substrate. The reaction temperature is 35-40 degrees. The ratio of silica sol to water-based epoxy resin is 5:

1. After the reaction, take out 55-70%; The heating surface of the waste heat boiler is cleaned by air blowing before the coating is sprayed, and there is no need to treat the rust on the sprayed heating surface; Spraying at above 20 degrees, surface drying in 4 hours, actual drying in 24 hours; Spraying above 5 degrees, surface drying in 8 hours, actual drying in 48 hours; After the paint is sprayed and dried, 500-600℃ flue gas is introduced to cause the paint to undergo a chemical reaction and form a coating that resists coking and ash formation on the heated surface.

Citation Information

Patent Citations

  • Water wall refractory belt anti-coking paint

    CN102351553A

  • Water-based nano high-temperature-resistant thermal-insulation anticorrosive paint and preparation method thereof

    CN111138951A

  • Formula and production process of decoking coating for kiln roller

    CN111363387A

  • Anti-coking and anti-corrosion treatment agent for boiler, and preparation method and application thereof

    CN111559907A

  • Aerosol type rust conversion spray with rust and preparation method thereof

    CN112522688A